2021
DOI: 10.1038/s41598-020-80880-3
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum doped zinc oxide deposited by atomic layer deposition and its applications to micro/nano devices

Abstract: This work reports investigation on the deposition and evaluation of an aluminum-doped zinc oxide (AZO) thin film and its novel applications to micro- and nano-devices. The AZO thin film is deposited successfully by atomic layer deposition (ALD). 50 nm-thick AZO film with high uniformity is checked by scanning electron microscopy. The element composition of the deposited film with various aluminum dopant concentration is analyzed by energy-dispersive X-ray spectroscopy. In addition, a polycrystalline feature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 68 publications
2
13
0
Order By: Relevance
“…In order to observe microstructure and film thickness simultaneously, the cycle number of the ZnO and AZO film were scaled down to 150. As shown in Figure 5 a,b, both the ZnO and AZO film exhibit a polycrystalline lattice structure, which is consistent with previously-reported works [ 34 , 35 ]. Noticeably, the thickness of the AZO film (18 nm) is thinner than that of the ZnO film (20 nm).…”
Section: Resultssupporting
confidence: 91%
“…In order to observe microstructure and film thickness simultaneously, the cycle number of the ZnO and AZO film were scaled down to 150. As shown in Figure 5 a,b, both the ZnO and AZO film exhibit a polycrystalline lattice structure, which is consistent with previously-reported works [ 34 , 35 ]. Noticeably, the thickness of the AZO film (18 nm) is thinner than that of the ZnO film (20 nm).…”
Section: Resultssupporting
confidence: 91%
“…This result is similar to other reported results with AZO thin films grown by other methods. [8,13,19,21,23,29,31,32,35,36,[39][40][41][42]44,[47][48][49][50][51][52][53][54][55][56][57][58] The Hall measurement results are listed in Table 4; from this table, it can be found that the higher value of conductivity and carrier concentration were achieved at 3 wt% doping concentrations as shown in Figure 8…”
Section: Electrical Studymentioning
confidence: 99%
“…[7,11,12,13,[15][16][17]19,28,30,[32][33][34][38][39][40][41][42][43][44][45][46][47][48][49][50][51] The conductivity and carrier concentration increased with increasing the aluminum, which is similar to other reported results by other methods. [8,13,19,21,23,29,31,32,35,36,[39][40][41][42]44,[47][48][49][50][51][52][53][54][55][56]…”
Section: Comparison/significance Of the Current Work Over The Reporte...mentioning
confidence: 99%
See 2 more Smart Citations